Exploring Conversational and Conventional Implicatures in Sara Bareilles’ Songs: She Used to Be Mine and Brave - Sutrisno, Bejo; Risa, Maya; Rachmawati, Budi (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This study investigates the role of implicature in shaping the interpretation and emotional impact of song lyrics, with a focus on Sara Bareilles’ "She Used to Be Mine" and "Brave". The objectives are threefold: (1) to examine how implicature contributes to lyrical meaning and emotional resonance, (2) to identify instances of implicature within the lyrics, and (3) to analyze the relationship between linguistic expression and thematic message. Adopting a qualitative research design and a content analysis approach, the study draws on two primary theoretical references: Analyzing Meaning: An Introduction to Semantics and Pragmatics (Textbooks in Language Sciences 5) for implicature characterization, and Grice’s Logic and Conversation as the principal framework for categorizing implicatures. The analysis identifies four types of implicature—Conventional Implicature (CI), Generalized Conversational Implicature (GCI), Particularized Conversational Implicature (PCI), and Scalar Implicature (SI)—present in both songs. Findings reveal that "She Used to Be Mine" predominantly employs Conventional Implicature (78%) and Scalar Implicature (60%), aligning with its introspective and reflective tone. In contrast, "Brave" relies more heavily on Generalized Conversational Implicature (56%) and Particularized Conversational Implicature (63%), reinforcing its motivational and empowering message. These results highlight the nuanced role of implicature in shaping both the interpretive depth and emotional impact of musical discourse.